Unraveling ecophysiological mechanisms in potatoes under different irrigation methods: A preliminary field evaluation - Silva Díaz, C.; Ramírez, D.; Rodríguez Delfin, A.; Mendiburu, F. de; Rinza, J.; Ninanya, J.; Loayza, H.; Quiróz, R. (MDPI, 2020)
Potatoes—a global food security and staple crop—is threatened by dry spells in drought-prone areas. The use of physiological thresholds to save water while maintaining a reasonable tuber yield has been proposed, but their effects on physiological performances and usefulness under different irrigation methods are yet to be evaluated. In this study, photosynthetic traits were monitored to assess the effect of water restriction and rewatering under drip (DI) and furrow (FI) irrigations. The treatments consisted of two maximum light-saturated stomatal conductance (g s_max ) irrigation thresholds (T2: 0.15 and T3: 0.05 mol H2O m −2 s −1 ) compared with a fully irrigated control (g s_max > 0.3 mol H2O m −2 s −1 ). DI used less water than FI but promoted early senescence and low percentage of maximum assimilation rate (PMA) at late developmental stages. FI caused no yield penalization in T2 and higher recovery of carbon isotope discrimination and PMA than DI. It is suggested that moderate water quantities of early and frequently water pulses in the irrigation, promote short-term water stress memory improvement, senescence delay and more capability of recovery at late stages.